Establishing logistics start-up companies: the role of institutions - Tóth, Ákos; Pesti, István (Advanced Logistic Systems - Theory and Practice, 2024)
The article examines how start-up companies in the transportation and warehousing sector can be encouraged by institutions from a macroeconomic perspective. The assumption is that start-ups are more likely to be successful in countries with higher quality institutional systems. In this article, the statistical data of the EU member states are compared using comparative analytical methods, followed by tests using econometric models to evaluate the results. On the one hand, the World Governance Indicator, Human Development Index, and International Property Rights Index of the examined European countries, and on the other hand Hit Horizon and EU startup industry databases are used to answer the puzzle. The assumption is that institutions play an important role in the success of start-up companies in the transportation and warehousing sectors.